2018
DOI: 10.1371/journal.pone.0205165
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical symptoms, gastric motility and fat intake in the early chronic pancreatitis patients with anti-acid therapy-resistant functional dyspepsia patients

Abstract: BackgroundThere was no available data concerning the clinical differentiation between the updated definition of early chronic pancreatitis (ECP) and anti-acid therapy-resistant functional dyspepsia (RFD).AimsWe aimed to determine whether clinical symptoms, gastric motility, psychogenic factors and fat intake can help distinguish early chronic pancreatitis (ECP) from anti-acid therapy-resistant functional dyspepsia patients with pancreatic enzyme abnormalities (RFD-P) and anti-acid therapy-resistant functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 45 publications
(56 reference statements)
7
31
0
Order By: Relevance
“…On average, functional dyspepsia accounts for 80% of dyspepsia [ 1 , 28 ]. Early chronic pancreatitis theoretically accounts for at least 19.6% of the whole dyspeptic population, because the study performed in Japan showed that approximately 24.5% of functional dyspepsia is early chronic pancreatitis [ 27 ]. Another study performed in Spain showed that the percentage of early-stage chronic pancreatitis, with three or four criteria of EUS for chronic pancreatitis, was 15.9% of the whole dyspeptic population, as seen in Figure 1 of that article (34/213 cases) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On average, functional dyspepsia accounts for 80% of dyspepsia [ 1 , 28 ]. Early chronic pancreatitis theoretically accounts for at least 19.6% of the whole dyspeptic population, because the study performed in Japan showed that approximately 24.5% of functional dyspepsia is early chronic pancreatitis [ 27 ]. Another study performed in Spain showed that the percentage of early-stage chronic pancreatitis, with three or four criteria of EUS for chronic pancreatitis, was 15.9% of the whole dyspeptic population, as seen in Figure 1 of that article (34/213 cases) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the chronic pancreatitis group, 60% of patients had early-stage chronic pancreatitis [ 26 ]. The other study enrolled 100 consecutive patients with functional dyspepsia and showed that approximately 24% were attributable to EUS-diagnosed early chronic pancreatitis [ 27 ]. However, these two studies lacked data on the overlap between Helicobacter pylori and early chronic pancreatitis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently Wakabayashi et al reported that nearly half of patients with proton pump inhibitor (PPI)-resistant FD had abnormalities in their pancreatic enzymes. 58 Interestingly, half of these FD patients had pancreatic enzyme abnormalities compatible with a diagnosis of ECP, suggesting that PPI-resistant FD cannot be differentiated from ECP on the basis of clinical symptoms alone: endosonography must be used to identify the unique EUS characteristics of these diseases. Interestingly, Yamawaki et al reported that EUS scores tended to be low in patients with refractory FD.…”
Section: Relationship Between Early Chronic Pancreatitis and Fdmentioning
confidence: 99%
“…( 2 ) ECP is considered to be early stage of chronic pancreatitis and exhibits symptoms similar to FD in Japan. ( 2 , 3 ) Since epigastric pain in ECP patients was improved by the treatment for chronic pancreatitis and aggravated by therapeutics targeting of FD, a precise diagnosis of ECP is critical to control clinical symptoms in ECP patients and to prevent this disease from advancing into chronic pancreatitis. ( 4 ) There were no available data about the differences between ECP and functional dyspepsia with pancreatic enzyme abnormalities (FD-P) patients.…”
Section: Introductionmentioning
confidence: 99%